2014
DOI: 10.1007/s11199-014-0441-1
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Involvement, Objectified Body Consciousness, Body Shame, and Sexual Assertiveness in College Women and Men

Abstract: Given the heightened attention to visual impression management on social media websites, previous research has demonstrated an association between Facebook use and objectified body consciousness among adolescent girls and young women in various Western countries, including the U.S. (e.g., Meier & Gray, 2013). The current study aimed to test whether both young women and men using social networking sites are vulnerable to objectified body consciousness, and to extend this line of research to sexual health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 63 publications
13
155
2
2
Order By: Relevance
“…Internet exposure has been shown to be associated with body surveillance among female adolescents and pre-adolescents, and male and female college students (Fardouly et al 2015a;Manago et al 2015;Meier and Gray 2014;Slater 2013, 2014), as well as with body shame among young adults (Melioli et al 2015). In addition, in this last study, body shame mediated the relationship between Internet use and bulimic symptoms (Melioli et al 2015).…”
Section: Self-objectification Theorymentioning
confidence: 47%
See 1 more Smart Citation
“…Internet exposure has been shown to be associated with body surveillance among female adolescents and pre-adolescents, and male and female college students (Fardouly et al 2015a;Manago et al 2015;Meier and Gray 2014;Slater 2013, 2014), as well as with body shame among young adults (Melioli et al 2015). In addition, in this last study, body shame mediated the relationship between Internet use and bulimic symptoms (Melioli et al 2015).…”
Section: Self-objectification Theorymentioning
confidence: 47%
“…Regarding young adults, among US female college students, duration of Facebook use was associated with disordered eating (Mabe et al 2014), and Facebook involvement was found to be associated with objectified body consciousness, which in turn was associated with body shame (Manago et al 2015). Similarly, among a sample of French young women, body image avoidance and disordered eating were associated with social networking website use; however these relationships were not replicated among young men .…”
Section: Correlational and Longitudinal Studiesmentioning
confidence: 90%
“…Being perceived as sexual may increase vulnerability to being perceived as lacking in human nature, as focus on women's sexual appearance increases the likelihood that they will be categorised as lacking in warmth, morality and competence (Hellick et al, 2011). Although most research has been carried out on the consequences for women of being treated as sex objects, recent studies demonstrate commensurate ill-effects on men who have been objectified in this way (Manago et al, 2015). Gender stereotypes imposed on female robots may aid sexist objectification (Richardson, 2015;Robertson, 2010).…”
Section: Sexbots Customisation and Inclusion In The Moral Circlementioning
confidence: 99%
“…Multiple studies also demonstrate that teens are hyper-aware of the public nature of their social media profiles, with users frequently commenting on sexual attractiveness, or lack thereof, when peers post provocative photos (Manago, Ward, Lemm, Reed, & Seabrook, 2015;Ringrose & Renold, 2012;Stevens et al, 2014). This anticipation of appreciative or negative feedback causes some adolescents to avoid posting photos of themselves, while others post sexually suggestive image to gain "likes," in what Magano deems "self-commodification" online (Manago, Graham, Greenfield, & Salimkhan, 2008;Manago et al, 2015;Stevens et al, 2016).…”
Section: Sexual Content In Social Mediamentioning
confidence: 99%
“…This anticipation of appreciative or negative feedback causes some adolescents to avoid posting photos of themselves, while others post sexually suggestive image to gain "likes," in what Magano deems "self-commodification" online (Manago, Graham, Greenfield, & Salimkhan, 2008;Manago et al, 2015;Stevens et al, 2016).…”
Section: Sexual Content In Social Mediamentioning
confidence: 99%